Maternal thyroid function in multiple pregnancies – a systematic review - Zgliczynska, Magdalena; Ostrowska, Magdalena; Szymusik, Iwona; Ciebiera, Michal; Kosinska-Kaczynska, Katarzyna (Frontiers in Endocrinology, 2023)
Background The function of the thyroid gland during pregnancy undergoes physiological changes to ensure the proper amount of thyroid hormones for both the pregnant woman and the fetus. Multiple pregnancies (MP) are characterized by specific differences compared to single pregnancies, e.g., higher concentrations of human chorionic gonadotropin, which also affect thyroid function. The aim was to collect available knowledge on maternal thyroid function in MP. Methods We have systematically searched three databases: the PubMed/MEDLINE, Scopus and the Cochrane Library. The last search was run on the 4th of August 2022. We included full-text original observational and experimental studies written in English. Case reports, editorials, letters, conference abstracts, reviews and meta-analyses were excluded. No time criterion was established. Studies were considered eligible if at least one maternal thyroid function test was performed and reported. Studies on MP with a co-existing mole were excluded. The risk of bias was assessed with the use of the AXIS tool. The qualitative synthesis of evidence was applied. Results The search strategy resulted in the identification of 821 manuscripts. After removing duplicates, we screened the titles and abstracts of 552 articles, out of which 57 were selected for full-text analysis. Finally, 12 articles were included in the review. They were conducted in 6 different countries and published between the years 1997 and 2022. The number of examined women with MP ranged from 9 to 1 626. Discussion and conclusions Thyroid function differs between women with MP and SP. Scarce data are available on the topic, but MPs are most likely characterized by higher HCG levels, which influences thyroid-stimulating hormone and free thyroid hormone levels. These differences are mainly expressed in the 1st trimester of pregnancy. Separate population-based reference ranges are needed to correctly diagnose thyroid diseases in MP and to avoid unnecessary treatment. Further research is needed to fill the knowledge gaps.